التفريق القضائي بين الزوجين بسبب الإعسار عن النفقة: دراسة فقهية مقارنة - أحمد، حسن عثمان (الجامعة الإسلامية - إدارة العلاقات والبحوث والمشاريع, 2018)
The judge has the power of separating between the spouses if necessary, especially if one of the spouses asks for separation due to a defect in the contract, or there is a harm which the wife cannot endure it and cannot stay with her husband as long as that harm exists either it is word or deed, Whether it is food, clothing, housing or dowry, and the matter is brought to him. The judge gets his power from his general responsibility of lifting the injustice over the people. This study addresses the legitimate merits of acting the separation by the authority when a man failed to pay alimony (النفقة) because of insolvency. The object of this study is to know generally the rules of separating spouses by the judge, and to show the role of judge in solving family problems when it raised to him, and displayig the rules of insolvency, and to declare that Islam did not neglect woman and gave her right in the divorce and allowed her to demand separation from the judge. The method of this study is a descriptive and inductive method, by telling: what The Fuqaha, a said, evidences, and discussions if they are there, and then preferring between them without fanatical doctrine. The most important calculations of this study are the following ones: First: Islam allowed marriage and urged everyone who is able to marry and then maintained the continuity of married life on the approach of Islam, and eliminated the principle of non-separating between men and women in the common human value, and gave women good rights as well as their duties. Secondly: the Islamic law gave the husband the right to divorce by his own will, and no one else participates in it, except by proxy or authorization from him. However, the Islamic law did not ignore the right of the woman, and gave her the right to demand separation from the judge in cases where the marital relationship becomes a source of misery. Third: The judge separates between the spouses if there is a shortfall in the necessary compulsory alimony, whether it is food or clothing or housing or dowry, and raised the matter to him. This research consists of four sections. The first section is all about the definitions of separation, judgment, and insolvency. In the second section the researcher clears the definition of alimony as a language and a terminology. The third section the researcher dealt with doctrines of the jurists about the rule of separating when the husband fails to pay and spend his wife. Also the researcher talked about the rule of separating between the absent husband and his wife on the same problem (alimony). The forth section mentioned the conditions of separating for non-spending, and described the separating as insolvency.
للقاضي سلطة التفريق بين الزوجين إذا اقتضى الأمر ذلك، سواء كان بالقول أو بالفعل، أو تقصيره في إيفائها القدر الضروري من النفقة الواجبة من طعام أو كسوة أو مسكن أو مهر إن رفعت الأمر إليه. والقاضي يستمدّ سلطته هذه من ولايته العامة في رفع الظلم. وهذه الدراسة تتناول الحيثيات الشرعية المنظور إليها عند ممارسة هذه السلطة وإجرائها في حالات عجز الزوج عن الإنفاق لعسر. والهدف من هذا البحث هو معرفة أحكام التفريق بين الزوجين الذي يجريه القاضي بوجه عام، وتوضيح دور القاضي في حل مشاكل الأسر إذا رفعت إليه. وتوضيح أحكام الإعسار بالنفقة، وبيان أن الإسلام لم يهمل جانب المرأة وحقها في الطلاق، بل أباح لها طلب التفريق إلى القاضي. والمنهج المتبع في إعداد هذا البحث هو المنهج الوصفي الاستقرائي، وذلك بذكر أقوال الفقهاء والأدلة والمناقشات إن وجدت، ثم الترجيح بينها بدون تعصب لمذهب معين وسبب الترجيح. ومن أهم نتائجه التي تمّ التوصّل إليها ما يلي: أولاً: حرصت الشريعة الإسلامية كل الحرص على حماية الحياة الزوجية من التفكك والفوضى والظلم، وهيأت سبلاً عديدة لإصلاح الزوجية في حالة النشوز، وإذا عجزت عن ذلك والمصلحة تقتضي التفريق بين الزوجين فرق القاضي بينهما. ثانياً: أعطت الشريعة الإسلامية للزوج حق الطلاق بإرادته المنفردة د، إلا أنها لم تغفل حق المرأة فأعطتها حق طلب التفريق من القاضي. ثالثاً: يفرق القاضي بين الزوجين إذا وجد تقصيرا من الزوج في إيفائها القدر الضروري من النفقة الواجبة سواء كان ذلك طعاماً أو كسوة أو مسكناً أو المهر ورفعت الأمر إليه. ويتكون البحث من أربعة مباحث، يتناول المبحث الأول تعريف التفريق، والقضاء، والإعسار، والمبحث الثاني تعريف النفقة لغة واصطلاحاً، ومشروعيتها. وفي المبحث الثالث يتناول البحث مذاهب الفقهاء في حكم التفريق لعدم الإنفاق في حال عجز الزوج الحاضر عن الإنفاق على زوجته، وكذلك حكم التفريق بين الغائب وزوجته لعدم الإنفاق. وأما المبحث الرابع فذكر فيه شروط التفريق لعدم الإنفاق، ووصف الفرقة بالإعسار.
Keywords: التفريق بين الزوجين -- الأحكام القضائية -- التفرقة بالإعسار -- حق الطلاق -- حقوق المرأة -- حق النفقة